PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PROJECT BASED LEARNING DALAM MENINGKATKAN KETERAMPILAN DASAR BOGA SISWA SMKN 6 MAKASSAR - Qur’ani, Besse (Universitas Negeri Padang, 2020)
This study aims to develop learning tools based on project based learning in improving the basic skills of catering for students of SMKN 6 in Makassar. This type of research is the development of learning tools in the form of research and development. The tools developed include the syllabus, job sheets and student books. The development model used is a 4-D model with stages of define, design, develop and disseminate. Based on the results of the analysis conducted, the development of learning tools with the PjBL model is declared valid, practical and effective so that it is feasible to use, so it is necessary to consider criteria that include; (1) the results of the validity of PjBL-based learning tools after being evaluated and examined by experts produce valid categories for lesson plans and job sheets, while for student books in the category are very valid (very good); (2) student activities receive classical completeness in the category of very valid (very good), while for cognitive, affective and psychomotor learning outcomes students are in the valid category; and (3) student responses and management of learning in the classroom categories are very valid. The suggestions made in this study are (1) to fellow teachers to use the PjBL model as an alternative used in the learning process; (2) learning materials developed after improvements and revisions can be tested in several other schools based on the problem characteristics of each school.